Coaching, Peer Evaluation Skills, and Professional Development of Teachers in Secondary Schools in Calamba City, Laguna - Mulingtapang, Lourody G.; Astillero, Jeffrey A. (Edu Berkah Khatulistiwa, 2025)
Coaching, peer evaluation skills, and professional development are crucial in enhancing teachers' competencies and effectiveness in the classroom. By providing them personalized support, coaching enables educators to improve their teaching methods, deal with obstacles, and use best practices. Coaching promotes a culture of ongoing learning and professional development by providing organized direction and feedback, eventually improving student outcomes. Effective coaching integration enables teachers to cultivate reflective practices and adjust to changing educational needs. Peer evaluation abilities promote cooperation, helpful criticism, and self-improvement, all enhancing professional development. Teachers who participate in peer evaluation receive insightful feedback from their peers, which promotes a sense of collective accountability for high-quality instruction. By encouraging a culture of trust and professional discussion, this technique improves student involvement and refines teaching strategies. By providing insightful criticism, peer evaluation also assists instructors in identifying areas for growth while highlighting their strengths. The combination of coaching, peer evaluation, and professional development creates a dynamic system that supports lifelong learning among teachers. Professional development programs that include these components guarantee that teachers maintain current knowledge, creative teaching methods, and a growth mentality. Adopting these strategies helps schools foster a reflective and cooperative learning environment that benefits educators and learners. The total quality of education is eventually strengthened by funding coaching and peer evaluation, which also equips educators to successfully negotiate the challenges of contemporary classrooms.